Role of ultrasound and color Doppler in diagnosis of ectopic pregnancy and to differentiate from corpus luteum cyst of pregnancy - Pooja Chowdary; Anilkumar Sakalecha; Anees Dudekula; Madan Kumar KN (Asian Journal of Medical Sciences, 2024)
Background: Ectopic pregnancy is the leading cause of direct maternal deaths. Ectopic pregnancy and corpus luteum cyst are two most common differential diagnoses in a patient with urine pregnancy test (UPT) positive and no sonographic evidence of intrauterine pregnancy. Internal echotexture and color Doppler features of the cyst wall are also considered in an attempt to differentiate the tubal ring of an ectopic pregnancy from that of a corpus luteum. Aims and Objectives: The aim of this study was to diagnose the presence of ectopic pregnancy and to differentiate ectopic pregnancy from corpus luteum cyst using grayscale ultrasound and color Doppler findings. Materials and Methods: The prospective study was conducted in 46 patients who were referred to the Department of Radiodiagnosis in R.L Jalappa Hospital with UPT positive and clinical features suggestive of ectopic pregnancy. Results: Out of 46 patients, 33 were diagnosed with ectopic pregnancy and 13 with corpus luteum cyst. Ectopic pregnancies had thicker walls as compared to corpus luteum cysts. Most of the ectopic pregnancies had hyperechoic walls as compared to ovaries (63.6%) and endometrium (60.6%). Free fluid with echoes was seen in the pelvis in 59.4% ectopic pregnancies whereas most of the corpus luteum cysts (69.2%) had no free fluid. Most of the corpus luteum cysts (61.5%) had clear internal echotexture whereas ectopic pregnancies were mostly lacy or solid. Yolk sac was seen exclusively in ectopic pregnancy (30.3%). RI 0.7 was found to be highly specific for diagnosing ectopic pregnancy. Conclusion: Significant ultrasound parameters that aid in differentiating between the two include the thickness of the mass’s wall, the wall’s echogenicity in relation to the ovary and endometrium, the internal echotexture of the cystic mass, the presence of the yolk sac, and the presence of free fluid with echoes. It was shown that RI 0.7 has a very good specificity in identifying ectopic pregnancy.